2006
DOI: 10.1152/ajpregu.00052.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac baroreflex facilitation evoked by hypothalamus and prefrontal cortex stimulation: role of the nucleus tractus solitarius 5-HT2Areceptors

Abstract: We previously showed that serotonin (5-HT2) receptor activation in the nucleus of the tractus solitarius (NTS) produced hypotension, bradycardia, and facilitation of the baroreflex bradycardia. Activation of the preoptic area (POA) of the hypothalamus, which is involved in shock-evoked passive behaviors, induces similar modifications. In addition, previous studies showed that blockade of the infralimbic (IL) part of the medial prefrontal cortex, which sends projections to POA, produced an inhibitory influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…In addition, the PL/IL labeling, as was observed in the present study, was localized to lamina V ( Fig. 1D-F), occupying the cortical area that fits quite well the loci of electrical or chemical stimulation that evoked altered gastric motility, heart rate and blood pressure (Hurley-Gius and Neafsey, 1986;Sevoz-Couche et al, 2006;Hassan et al 2013 and. The retrograde labeling in M1 and M2 suggests that these corticomotor areas project to DVC.…”
Section: Tract-tracing and The Retrogradely Labeled Neuronssupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, the PL/IL labeling, as was observed in the present study, was localized to lamina V ( Fig. 1D-F), occupying the cortical area that fits quite well the loci of electrical or chemical stimulation that evoked altered gastric motility, heart rate and blood pressure (Hurley-Gius and Neafsey, 1986;Sevoz-Couche et al, 2006;Hassan et al 2013 and. The retrograde labeling in M1 and M2 suggests that these corticomotor areas project to DVC.…”
Section: Tract-tracing and The Retrogradely Labeled Neuronssupporting
confidence: 84%
“…In addition, mPFC is actively involved in autonomic regulation, as is evidenced by the decreased gastric motility, hypotension and bradycardia following stimulation of the prelimbic (PrL) and infralimbic cortices (IL) (Hurley-Gius and Neafsey, 1986;Heidbreder and Groenewegen, 2003;Sevoz-Couche et al, 2006;Hassan et al, 2013), the two important subdivisions of mPFC. Previous studies indicated that this autonomic effect might be mediated through divergent pathways including mPFC projections to brain stem dorsal vagal complex (DVC), which is composed of nucleus of solitary tract (Sol), the dorsal motor nucleus of vagus (DMV) and area postrema, either directly or indirectly via relay of such structures as amygdala and hypothalamus (Saper, 2004;Gabbott et al, 2005;Sevoz-Couche et al, 2006;Mussa and Verberne, 2013). Thus, DVC plays a pivotal role in mediating descending control of autonomic activities.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the same brain stem nuclei [e.g. the nucleus tractus solitarius (Sevoz-Couche et al 2006) regulate both the inflammatory and baroreflex systems. Among people who are gravely ill, reduced HRV is a predictor of death (Bluzaite et al 2006;Chan 2008;Christensen 2003;Politano et al 2008).…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…Although the characteristic neurochemical, ultrastructural and functional properties of target neurons in the NTS and VLM receiving synaptic input from IL cortex need to be fully defined in future studies (Resstel and Corrêa, 2006a,b;Sevoz-Couche et al, 2006), one important question emerges from the present data: 'What are the functional implications of the comparatively modest IL input to THϩ neurons in both the NTS and rVLM? ' Immunocytochemical evidence indicates that the descending projections from IL cortex would provide 'excitatory' glutamatergic input to the dendritic shafts and spines of neurochemically diverse target neurons in both NTS and rVLM (Torrealba and Müller, 1999).…”
Section: Functional Implicationsmentioning
confidence: 93%